2014
DOI: 10.1039/c3mt00309d
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, distribution, metabolism and excretion of selenium following oral administration of elemental selenium nanoparticles or selenite in rats

Abstract: A suspension of nanoparticles of BSA-stabilized red amorphous elemental selenium (Se) or an aqueous solution of sodium selenite was repeatedly administered by oral gavage for 28 days at 0.05 mg kg À1 bw per day (low dose) or at 0.5 mg kg À1 bw per day (high dose) as Se to female rats. Prior to administration, the size distribution of the Se nanoparticles was characterized by dynamic light scattering and transmission electron microscopy, which showed that the particles' mean diameter was 19 nm and ranged in siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 35 publications
6
70
0
Order By: Relevance
“…The samples were centrifuged and stored as plasma at -70°C with EDTA and were analysed together. The SePP was determined by affinity HPLC with ICP-MS detection and isotope dilution quantification of Se using a method previously described in detail [19]. …”
Section: Methodsmentioning
confidence: 99%
“…The samples were centrifuged and stored as plasma at -70°C with EDTA and were analysed together. The SePP was determined by affinity HPLC with ICP-MS detection and isotope dilution quantification of Se using a method previously described in detail [19]. …”
Section: Methodsmentioning
confidence: 99%
“…A Philips CM100 transmission electron microscope (TEM) (FEI, Eindhoven, the Netherlands), operating at 80 kV accelerating voltage was then used to image the size and shape of the SeNPs. 13 animals Adult male albino rats of the Wistar strain weighing 110-140 g were obtained from the Holding Company for Biological Products and Vaccines (VACSERA, Cairo, Egypt). After acclimatizing for 7 days, the animals were divided into seven groups (with seven rats per group) and housed in wire-bottomed cages in a room kept at 25°C±1°C and under a 12 hour light/12 hour dark cycle.…”
Section: Preparation and Characterization Of Senpsmentioning
confidence: 99%
“…A STZ-SeNPs group consisted of diabetic rats treated with SeNPs at 0.1 mg of SeNPs/kg administered orally. 13 A STZ-insulin (Ins) group consisted of diabetic rats treated with standard drug insulin (6 U/kg, subcutaneous [sc] administration). Finally, a STZ-SeNPs-Ins group consisted of diabetic rats treated with SeNPs and the standard drug insulin.…”
Section: Experimental Designmentioning
confidence: 99%
“…Recently, Loeschner et al reported the presence of elemental selenium in the liver (17% of total Se) and kidneys (40% of total Se) of rats fed 0.5 mg Se as selenite per kg of body weight per day for 28 days. 36 The species was detected by anion exchange HPLC and ICP-MS after being reduced in situ with sodium sulfite to the selenosulfate anion. Elemental Se was also detectable in the liver and kidneys of rats fed control and low Se diets, although at much lower concentrations (<10% of total Se).…”
Section: Resultsmentioning
confidence: 99%